Navigating Government Funding During a Pandemic: A Study on Nonprofits’ Receipt of Disaster Relief Funds - Chen Xintong; Yang Zheng (Nonprofit Policy Forum)
American communities have been the hardest hit by the COVID-19 pandemic. The collaboration between governments and nonprofits is needed to satisfy the needs of the American communities. This article investigates the organizational factors of nonprofits that contribute to the obtainment of government disaster relief funds in the context of the COVID-19 pandemic by surveying nonprofits whose main offices were located in California. The findings show that, in general, having internal professionals in fundraising, and having previous experience in government applications contribute to the successful receipt of government relief funds. Moreover, different factors are associated with the receipt of relief funds from different levels of government. This article offers valuable insights to government and nonprofit funding relations and how their collaboration can enhance community resilience during times of disasters.